2022
DOI: 10.1101/2022.01.31.478157
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In silico analysis of predicted differential MHC binding and CD8+ T-cell immune escape of SARS-CoV-2 B.1.1.529 variant mutant epitopes

Abstract: Introduction: The B.1.1.529 (Omicron) SARS-CoV-2 variant has raised global concerns due to its high number of mutations and its rapid spread. It is of major importance to understand the impact of this variant on the acquired and induced immunity. Several preliminary studies have re-ported the impact of antibody binding and to this date, there are few studies on Omicron CD8+ T-cell immune escape. Methods: We first assessed the impact of Omicron and B.1.617.2 (Delta) variant mutations on the SARS-CoV-2 spike epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Riesgo‐Ferreiro et al reported that Omicron exhibits numerous amino acid substitutions that result in increased immunogenicity. 80 Studies show that Omicron shares numerous mutations and deletions with other strains that are well‐known for increasing viral transmissibility and binding affinity. It is also hypothesized that these mutations assist with immune evasion and antibody escape.…”
Section: Discussionmentioning
confidence: 99%
“…Riesgo‐Ferreiro et al reported that Omicron exhibits numerous amino acid substitutions that result in increased immunogenicity. 80 Studies show that Omicron shares numerous mutations and deletions with other strains that are well‐known for increasing viral transmissibility and binding affinity. It is also hypothesized that these mutations assist with immune evasion and antibody escape.…”
Section: Discussionmentioning
confidence: 99%